How to submit MS proteomics data to ProteomeXchange via the PRIDE database. Issue 20 (21st August 2014) - Ternent, Tobias; Csordas, Attila; Qi, Da; Gómez‐Baena, Guadalupe; Beynon, Robert J.; Jones, Andrew R.; Hermjakob, Henning; Vizcaíno, Juan Antonio
<x xml:space="preserve">Abstract</x> The ProteomeXchange (PX) consortium has been established to standardize and facilitate submission and dissemination of MS‐based proteomics data in the public domain. In the consortium, the PRIDE database at the European Bioinformatics Institute, acts as the initial submission point of MS/MS data sets. In this manuscript, we explain step by step the submission process of MS/MS data sets to PX via PRIDE. We describe in detail the two available workflows: 'complete' and 'partial' submissions, together with the available tools to streamline the process. Throughout the manuscript, we will use one example data set containing identification and quantification data, which has been deposited in PRIDE/ProteomeXchange with the accession number PXD000764 (http://proteomecentral.proteomexchange.org/dataset/PXD000764).